PENGUKURAN APTITUDE DENGAN UJI KRAEPELIN MENGGUNAKAN METODE LINEAR CONGRUENTIAL METHOD (LCM) - Qatrun Nada; Muhammad Arhami; Zulfan Khairil Simbolon (Politeknik Negeri Lhokseumawe, 2022)
Psychological tests are an important need in various spaces of human life. Not only related to matters of a clinical nature, psychological tests are also used in the workspace. Psychological tests are carried out as an effort to find out by knowing more about a person's personality. One of the methods used by psychologists is Kraepelin to get personality types. In practice, psychological tests in understanding an object, namely humans with all their attitudes and behavior, still use the old way. Psychological tests still use sheets or series of questions given to related objects and the calculation of results or assessments is still done manually. Errors in the assessment will affect the results so that it will lead to inappropriate perceptions. Making questions requires time and high accuracy, so the system is built using the Linear Congruential Method (LCM). LCM method is used to generate random numbers with better access time performance in terms of complexity and optimality. The 20 minute test application consists of 40 columns and 60 rows of questions with a time limit of 30 seconds for each column. The website-based Kraepelin test application can support all related parties, both the test organizers and test takers, to get real-time and accurate test results by applying the Kraepelin test using the LCM method. The implementation of the Kraepelin test is in accordance with the purpose of using the test, namely as a tool to measure aptitude (speed, accuracy, stability and work endurance). Based on the test results, the calculation of the score using the system will be faster with a calculation time of 2 seconds while the manual calculation is 5 minutes.